2016
DOI: 10.3390/rs8050372
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Forest Mapping at Individual Tree Levels from Terrestrial Laser Scanning Point Clouds with a Hierarchical Minimum Cut Method

Abstract: Abstract:Laser scanning technology plays an important role in forest inventory, as it enables accurate 3D information capturing in a fast and environmentally-friendly manner. The goal of this study is to develop methods for detecting and discriminating individual trees from TLS point clouds of five plots in a boreal coniferous forest. The proposed hierarchical minimum cut method adopts the detected trunk points that are recognized according to pole like shape segmentation as foreground seed points and other po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…Principally, a rapid and automated measurement of objects in the three-dimensional space and the creation of dense 3D-point clouds at a millimeter-resolution are possible using terrestrial laser scanning (TLS) [14][15][16][17]. Different algorithms for the automatic detection of individual trees in 3D-point clouds have recently been developed and provide detection rates clearly exceeding 90% [10,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principally, a rapid and automated measurement of objects in the three-dimensional space and the creation of dense 3D-point clouds at a millimeter-resolution are possible using terrestrial laser scanning (TLS) [14][15][16][17]. Different algorithms for the automatic detection of individual trees in 3D-point clouds have recently been developed and provide detection rates clearly exceeding 90% [10,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Different algorithms for the automatic detection of individual trees in 3D-point clouds have recently been developed and provide detection rates clearly exceeding 90% [10,16,18,19]. Existing studies on automatic DBH measurement from TLS point-clouds have reported root mean squared deviations (RMSD) between measured and fitted DBH values ranging from 0.7 to 7.0 cm [10,18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, those results are based on one single 0.07 ha sample plot, containing only 14 trees (all of them 140 year old beeches), representing a very low tree density of only 200 trees ha −1 . Other studies reported overall accuracies (the metric is called "completeness" in that reference) between 86.9% and 89.0% for dense but homogeneous bamboo stands [45] and detection rates of 90.4% in boreal coniferous forests [26] (the metric is called "recall" in that reference). Comparison of our multi-scan TLS based overall accuracies with measures obtained by single-scan TLS or airborne laser scanning (ALS) may be criticized as unfair, because the latter data are associated with lower measurement intensity.…”
Section: Tree Detectionmentioning
confidence: 99%
“…Compared with airborne laser scanning and field measurements, TLS can obtain accurate understory information, including a digital record of the three-dimensional structure of forests [3]. Many studies have demonstrated the high potential of TLS in forest inventory, including tree locations [1,[4][5][6], heights [2,3,7], diameters [2,3,6,[8][9][10][11][12][13][14][15], volumes [16][17][18], biomass [17,[19][20][21][22][23] and others forestry parameters [24][25][26][27]. In addition, the influence of scanner parameters on forestry parameter derivation has been studied [18,28].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, retrieving forestry parameters from terrestrial laser scanning (TLS) data has become an active area of research [1,2]. As an active remote sensing technology, TLS can provide a fast and efficient tool for obtaining a dense 3D point cloud dataset containing an immense number of three-dimensional points reflected from scanned objects.…”
Section: Introductionmentioning
confidence: 99%